Capacity Development Evaluation: The Challenge of the Results Agenda and Measuring Return on Investment in the Global South. (March 2016) - Vallejo, Bertha; Wehn, Uta
Summary: This study reviews the evaluation of capacity development, identifying capacity development (CD) modalities and the schools of evaluation currently in place. The research joins the results agenda debate, arguing that in dealing with CD interventions, pre-defined indicators fail to represent the process and the key elements that take CD recipients toward patterns of change. The study highlights the fact that CD deals with projects that, by their nature (consisting of change processes designed to initiate change in people, organizations, and/or their enabling environment), rely more on non-planned changes than on the pre-defined indicators and results to contribute to livelihood improvements and social transformation. The study recognizes the difficulty of evaluating CD under straightforward mechanisms. It concludes that the existing approaches are not adequate to truly capture or measure impact, as CD projects, restricted by previously agreed budgets, resources, and time frames, are usually not designed to evaluate the sustainability of change and its impact over the medium or long term. As resources are scarce, donor agencies and policy-makers need to know the value of CD in order to best prioritize their investments. However, due to the nature of these projects, measuring the return rate between the project cost and its impact remains a difficult task. There is a need for new, multi-path approaches to capturing changes in capacity in order to serve as a basis for decision-making regarding CD investments.